Respuesta :

Answer:

x = -2

Step-by-step explanation:

Simplifying

2x + -5x = 3x + 12

Combine like terms: 2x + -5x = -3x

-3x = 3x + 12

Reorder the terms:

-3x = 12 + 3x

Solving

-3x = 12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-3x + -3x = 12 + 3x + -3x

Combine like terms: -3x + -3x = -6x

-6x = 12 + 3x + -3x

Combine like terms: 3x + -3x = 0

-6x = 12 + 0

-6x = 12

Divide each side by '-6'.

x = -2

Simplifying

x = -2